The Influence of Islamic Spiritual Mindfulness on Social Emotional Maturity of Students at SMPN 9 Mandau - Nunung Masruroh; Risnawati Risnawati; M. Fikri Hamdani (UIN Fatmawati Sukarno Bengkulu, 2025)
Emotional-social maturity is a crucial aspect of adolescent development, playing a significant role in shaping positive character and the ability to face challenges. This study focuses on adolescents aged 13–15 years, a transitional period marked by complex emotional and social dynamics influenced by internal factors such as hormonal changes and external factors including evolving relationships and societal demands. Emotional-sosial maturity, characterized by the ability to adapt to one's environment, manage emotions, and accomplish developmental tasks, is essential for academic success and social interaction. However, challenges such as emotional instability, social conflicts, and low self-efficacy often hinder this development. This research explores the influence of Islamic spiritual mindfulness on emotional-social maturity among students in the context of Islamic Religious Education (PAI) at SMPN 9 Mandau. Mindfulness, rooted in the Islamic concept of *muraqabah*, emphasizes awareness of Allah’s constant presence, fostering self-control, gratitude, and emotional regulation. By incorporating mindfulness practices into PAI lessons, educators aim to enhance students' ability to manage emotions, reduce stress, and develop meaningful sosial interactions. Using a quantitative approach, this study investigates the correlation between Islamic spiritual mindfulness and emotional-social maturity. Prior studies indicate that heightened mindfulness contributes to improved emotional intelligence, reduced psychological distress, and better self-management skills. The findings are expected to provide strategic insights into integrating mindfulness into education, supporting students' holistic development, and addressing challenges in emotional-social growth effectively.